Forgeries, Falsifications, Fictions, Fälschungen?: Some Early Modern European "Vedas" - Sweetman, Will (Entangled Religions, 2024)
This article examines—and rejects—the idea that, in the course of the seventeenth and eighteenth centuries, Europeans who sought to obtain copies of the Vedas were repeatedly duped by having other works (purporting to be Vedas) passed off on them. The focus is on a text entitled "The Essence of the Yajur Veda," produced by a Pietist missionary, Christoph Theodosius Walther (1699-1741), and a Brahmin identified only as Krishna, published in a German missionary periodical in 1740. This text is examined in the context of a series of similar works produced by Indian intellectuals with, or at the behest of, European missionaries and colonial officials in the seventeenth and eighteenth centuries. Rather than seeing these works as fakes, it is argued here that they are better understood as the outcome of distinctive modes of composition, transmission, and translation of Indian religious literature emerging from the early modern encounter of Indian and European scholars.